IMPLEMENTASI ASAS DISPENSASI KAWIN DI WILAYAH HUKUM PENGADILAN TINGGI AGAMA PALU PERSPEKTIF MASLAHAH - Massadi, Massadi; Gassing, Abd. Qadir; Jafar, Usman; Salenda, Kasjim (Jurnal Diskursus Islam, 2018)
The results of the study revealed that the degree of election of marriage dispensation in the jurisdiction of the Religious High Court of Palu was motivated by several factors, namely the pregnancy occurrence, parents' concerns, economic, matchmaking, and culture when  was about to get married and still under-age so it had to firstly apply for dispensation of marriage to the religious court in accordance with Act No. 1 of 1974, Article 7 Paragraph (1) and (2) Concerning Marriage jo Compilation of Islamic Law Article 15 Paragraphs (1) and (2). The application of marriage dispensation was submitted to the court, then will be on trial and judge’s consideration in granting marriage dispensation which was not bound by the single positive law yet it was a consideration of justice, legal sociology and benefits that emphasized the implementation of maslahah principle as well.